Margarita Jara, Roberto Zariquiey, Pilar Valenzuela y Anna María Escobar (eds.). Spanish Diversity in the Amazon: Dialect and Language Contact Perspectives. Vol. 18. Brill’s Studies in the Indigenous Languages of the Americas. Leiden: Brill, 2023. 346 pp. - Vásquez Aguilar, Alonso (2024)
No presenta resumen